Stress and Resilience in Functional Somatic Syndromes – A Structural Equation Modeling Approach - Fischer, Susanne; Lemmer, Gunnar; Gollwitzer, Mario; Nater, Urs M. (PloS one, 2014)
Stress has been suggested to play a role in the development and perpetuation of functional somatic syndromes. The mechanisms of how this might occur are not clear. We propose a multi-dimensional stress model which posits that childhood trauma increases adult stress reactivity (i.e., an individual's tendency to respond strongly to stressors) and reduces resilience (e.g., the belief in one's competence). This in turn facilitates the manifestation of functional somatic syndromes via chronic stress. We tested this model cross-sectionally and prospectively. Young adults participated in a web survey at two time points. Structural equation modeling was used to test our model. The final sample consisted of 3'054 participants, and 429 of these participated in the follow-up survey. Our proposed model fit the data in the cross-sectional (χ2(21)  = 48.808, p<.001, CFI  = .995, TLI  = .992, RMSEA  = .021, 90% CI [.013.029]) and prospective analyses (χ2(21)  =  32.675, p<.05, CFI  = .982, TLI  = .969, RMSEA  = .036, 90% CI [.001.059]). Our findings have several clinical implications, suggesting a role for stress management training in the prevention and treatment of functional somatic syndromes.